Coping strategies and mental health outcomes of conflict-affected persons in the Republic of Georgia. (25th January 2016) - Saxon, L.; Makhashvili, N.; Chikovani, I.; Seguin, M.; McKee, M.; Patel, V.; Bisson, J.; Roberts, B.
Abstract : Aims: Adults who experienced the 1992 and 2008 armed conflicts in the Republic of Georgia were exposed to multiple traumatic events and stressors over many years. The aim was to investigate what coping strategies are used by conflict-affected persons in Georgia and their association with mental disorders. Method: A cross-sectional survey was conducted with 3600 adults, representing internally displaced persons (IDPs) from conflicts in the 1990s ( n = 1200) and 2008 ( n = 1200) and former IDPs who returned to their homes after the 2008 conflict ( n = 1200). Post-traumatic stress disorder, depression, anxiety and coping strategies were measured using the Trauma Screening Questionnaire, Patient Health Questionnaire-9, Generalised Anxiety and adapted version of the Brief Coping Inventory, respectively. Descriptive and multivariate regression analyses were used. Results: Coping strategies such as use of humour, emotional support, active coping, acceptance and religion were significantly associated with better mental health outcomes. Coping strategies of behavioural and mental disengagement, denial, venting emotions, substance abuse and gambling were significantly associated with poorer mental health outcomes. The reported use of coping strategies varied significantly between men and women for 8 of the 15 strategies addressed. Conclusions: Many conflict-affected persons in Georgia are still suffering mental health problems years after the conflicts. A number of specific coping strategies appear to be associated with better mental health and should be encouraged and supported where possible.